The 61Πu state of Na2 molecule - Grochola, Anna; Kubkowska, Monika K.; Jastrzębski, Włodzimierz; Kowalczyk, Paweł (Oficyna Wydawnicza Politechniki Wrocławskiej, 2006)
Excitation spectra of sodium dimer were analysed within the range 34200–36400 cm–1. The experiment was done using polarisation labelling spectroscopy technique. In the spectral region under investigation we found several vibrational progressions belonging to a single band system having the ground state of Na2 as the lower state. The upper state was of 1Π u symmetry as indicated by the presence of Q lines in the spectrum and basing on theoretical calculations it was identified as the 61Π u (3s + 4f) state. The Dunham coefficients and potential curve characterising this state were deduced from the observed spectra.
Optica Applicata, Vol. 36, 2006, nr 4, s. 469-473
Keywords: optyka; Na2 molecule; laser spectroscopy; electronic states; potential energy curves